A PWM method for single‐phase cascade multilevel inverters to reduce leakage ground current in transformerless PV systems. (22nd March 2016) - Vazquez, Gerardo; Martinez‐Rodriguez, Panfilo R.; Escobar, Gerardo; Sosa, Jose M.; Martinez‐Mendez, Rigoberto
Summary: A single‐phase cascade multilevel inverter is able to synthesize AC output voltages with considerably reduced harmonic distortion, which results in reduced size output filters. In addition, the amplitude of the output voltage in the cascade multilevel inverter topology is usually higher than in a single H‐Bridge inverter, which makes possible the power injection into the grid without a voltage boost stage. These benefits make cascade multilevel inverter a suitable topology for PV applications. However, cascade multilevel inverters may exhibit large leakage ground current in a grid‐connected PV transformerless system, which is caused by a variable voltage across the stray capacitances formed between the PV panel and ground. In this paper, a modulation strategy for the cascade multilevel inverter is proposed to deal with leakage ground currents arising in transformerless PV applications. Numerical and experimental results are performed to assess the effectiveness of the proposed modulation strategy in the reduction of leakage ground currents and improving the topology efficiency. Copyright © 2016 John Wiley & Sons, Ltd.